Repositioning Pragmatics in the Interpretation of Grammatical Constructions - Žic Fuchs, Milena (Array, 2014)
This plenary lecture addresses the true position of pragmatics within the framework of Cognitive Linguistics, with special reference to the notion of convention. Examples analyzed in order to elucidate the semantics/pragmatics interface used were: the English present perfect, the particle le in Mandarin and the 'pejorative' diminutive in Croatian. The currently existing pragmatical theoretical approaches (Grice, Wilson and Sperber) were analyzed and the point was raised that they do not cover enough implications from the domain of pragmatics. This particularly refers to relevance in 'contexts of situation' and relevance in 'contexts of culture', as well as constraints on inference that form the basis of conventionalization in languages.